Absorption enhancement of plasmonic thin film solar cell combined with nanocavity - M Nasar, Norasikin (2020)
Plasmonic thin film solar cells have been given a lot of attention from researchers for their absorption capabilities. This study focused on the design of plasmonic thin film solar cell so that the absorption can be optimized. The structures were developed with different materials, geometries and configurations through Finite Element Method via COMSOL Multiphysics software. In order to validate the simulation method, comparison with the results from the previous research has been done first. The proposed design in this study is to build thin film solar cell with the combination of nanoparticle and nanocavity. Positioning gold nanoparticle in plasmonic thin film solar cell was demonstrated in various positions and nanoparticle near the surface has shown to be trapping more light. Semi-ellipse which used as nanocavity shape created an especial surface allowing more of the incident light was absorbed into the solar cell. From these results, the proposed design were structured by using indium tin oxide (ITO), silicon and aluminum as layers in the thin film solar cell with combination of nanoparticle and nanocavity. The result has shown remarkable positive change in absorption rate. The absorption rate for thin film solar cell with only ITO, silicon and aluminum layer has shown lower than thin film solar cell with these layers and the combination of nanocavity and nanoparticle. Detail from the results of this study will support future fabrication on solar cell.